2019
DOI: 10.1063/1.5098766
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of energy band tunable tin germanium oxide electron transport layer for the SnS-based solar cells with 400 mV open-circuit voltage

Abstract: Tin germanium oxide, (Sn,Ge)O2, films were prepared using atomic layer deposition and tailored to a SnS absorber layer by incorporating various amounts of germanium into tin oxide to adjust band alignments at the interfaces of SnS/(Sn,Ge)O2 photovoltaic devices. Carrier concentrations of (Sn,Ge)O2 were suppressed from 1020 to 1018 cm−3 with germanium incorporation, with nitrogen doping further reducing carrier concentrations by another order of magnitude. Excellent tunability of both band energy levels and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 99%
“…However, despite significant efforts to improve the V OC , the highest V OC is still limited to ≈400 mV, resulting in conversion efficiency ( η) of 2−4%. [ 15,16 ] A recent study reported a η of 4.8% with a V OC of 330 mV for a p‐SnS/n‐TiO 2 heterojunction, [ 17 ] which is the highest reported value for any SnS‐containing solar cells; however, this value is much lower than the theoretical value of SnS homojunction solar cell ( η = 25% at a V OC of 985 mV). [ 18 ] This implies that a further increase in the V OC of SnS heterojunction solar cell is considerably difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4 The critical point (CP) energies of SnS ε 2 , we fit the values in Table 1 with the cubic polynomial functions. The fit results are listed in Table 2.…”
Section: E 0bmentioning
confidence: 99%
“…Stack-layered structures materials in IV-VI group bring remarkable properties, which show high anisotropy of electrical and optical properties along with principal directions [1][2][3][4]. Strong correlation between the lattice anisotropy and optical property is indispensable information for many technological applications such as solar cells [5,6], ion batteries [7], sensors [8], thermoelectric devices [9], photovoltaics [10], and nonlinear optical applications [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%